(3efThQ GdTQW hGdHWs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOhO bGFe GdOjf GjgG GdTjhN GdWgQI bO GYPQ fPjQ GdGNhI hGhLH GdMLI Ydi GdGee HGdMce GdeYLRI hGdHQGgjf GdHGgQI s
(3BNQgG (B:s
(3hGdYOd Ydi ef Cac Yfg jLMO Mbg hGdGjg JeJ HMeO hdi GdfYeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis